ICTs for Agriculture in Africa - Zyl, Omri Van; Alexander, Trish; Graaf, Liezl De; Mukherjee, Kamal (World Bank, Washington, DC, 2014)
The strategic application of information and communications technology (ICT) to the agricultural industry, the largest economic sector in most African countries, offers the best opportunity for economic growth and poverty alleviation on the continent. Food security is paramount for the survival of individuals, families, and ultimately nations, yet Africa's agriculture sector has been in decline over the past 40 years. African agriculture is predominantly rain-fed, has low-yielding production, and lacks access to critical information, market facilitation, and financial intermediation services. The role that ICT can play in addressing these challenges is increasing as personal ICT devices such as mobile phones or tablet are becoming more widely available. ICT, when embedded in broader stakeholder systems, can bring economic development and growth as it can help bridge critical knowledge gaps. Mobile technology, on the other hand, is increasingly being adopted as the technology of choice for delivery of ICT services and solutions. The wider adoption of ICT in agriculture is of strategic importance to five main stakeholder groups: businesses; farmers; researchers; government; and citizens. In identifying the ways in which ICT can help agriculture, it is useful to view the farming life cycle as a three-stage process: pre-cultivation; crop cultivation and harvesting; and crop cultivation and harvesting.